Genetical psychology and theory of discourse: an evolutive foundation of democracy in Habermas (Cadernos de Ética e Filosofia Política, 2019)
This paper intends to proceed to a reconstruction of the theory of communicative action through its option for a social evolutionary strategy of foundation, as well taking in account the profound consequences of this theory for the political and legal institutions of the structures related to social recognition. The psychological theories of Lawrence Kohlberg and Jean Piaget are investigated as sources which offer helpful conceptual instruments on realizing such theoretical strategy. The homologies suggested by Habermas between the ontogenetic development of children and the social evolution of modern societies (its philogenetics) make easier to understand the crises of democracy within these societies. At the same time, the accusations of ethnocentrism and idealism against the Theory of Discourse can also, under these points of view, find more satisfying answers.